Abdominal obesity is a modifier of the association between physical activity and metabolic syndrome: a case-control study - Karamzad, Nahid; Saghafi-Asl, Maryam; Asghari-Jafarabadi, Mohammad; Naghizadeh, Mahsa; Amiri, Parichehr; Mehralizadeh, Hossein (Progress in Nutrition, 2019)
Background: The role of physical activity (PA) in metabolic syndrome (MetS) is almost clear; however, the contribution of PA to lower MetS risk in the presence of abdominal obesity remains unknown. Therefore, the present study aimed to assess the role of PA as well as anthropometric indices in MetS among abdominally obese individuals. Methods: This age and gender-matched case–control study was conducted on 164 abdominally obese people of North-West of Iran (81 MetS and 83 population-based controls) aged 18-60 years in 2015. The long version of International Physical Activity Questionnaire (IPAQ) was applied to classify participants into three categories: low, moderate, and high level physical activity (PA). MetS was assessed according to Iranian National Obesity Committee criteria. Biochemical and anthropometric parameters were measured. Both bivariate and multivariate binary logistic regression models were used for data analysis. Results: The mean level of triglyceride, fasting blood sugar, systolic blood pressure, and diastolic blood pressure was significantly higher in cases than controls (P0.05). Multivariate binary logistic regression also showed no significant association between PA levels and MetS components among abdominally obese, even after adjusting for confounders (P>0.05). Anthropometric indices were not significantly different between the two groups (P>0.05). When stratified by BMI, there was no significant association between PA level and MetS incidence. Conclusion: Abdominal obesity seems to be an important factor diluting the association of PA with MetS. In other words, waist circumference may play a mediator role in the association of PA level with MetS.